A low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete and preparation method thereof
By using large amounts of fly ash in ultra-high performance concrete, optimizing aggregate grading, adding regenerated coarse aggregate and steel fibers, and applying expansion agents and shrinkage agents, the problems of high cost and high shrinkage rate of UHPC materials are solved, and high strength, low shrinkage and low cost effects are achieved.
Patent Information
- Application Number
- CN202411918789.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing ultra-high performance concrete (UHPC) has limited its wide application in structural engineering due to its high material cost and high shrinkage rate.
The ultra-high performance concrete of low-shrinkage mixed steel fiber is used to replace cement by regenerating aggregates with high-performance fly ash, optimize the grading of air-accumulated sand and regenerated fine aggregates, add regenerated coarse aggregates and steel fibers, and use expansion agents, reducers and other admixtures to adjust the shrinkage performance of the concrete.
High-strength, low-shrinkage, and low-cost ultra-high-performance concrete is achieved, which reduces cement usage, reduces carbon dioxide emissions, and improves the durability and engineering applicability of the material.
Smart Images

Figure CN119349962B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, and in particular to a low-shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete and a preparation method thereof. Background Art
[0002] Ultra-high-Performance Concrete (UHPC) is a new type of concrete material with high strength, high toughness and high durability. It has broad application prospects in modern engineering structures such as long-span bridges, undersea tunnels and deep underground projects. Compared with ordinary concrete, ultra-high-performance concrete has good mechanical properties and durability. Thanks to the fact that UHPC is made based on the theory of close particle packing, it has lower porosity and better density. At the same time, the addition of high-efficiency water reducer generally makes its water-cement ratio lower than 0.20, so that UHPC exhibits better compressive, tensile, flexural and impact and explosion resistance. At present, in order to reduce the defects of concrete itself, UHPC mostly uses fine aggregate with a particle size of less than 2.5mm and does not contain coarse aggregate, but fine aggregate has the problem of high cost and difficulty in obtaining. In addition, because UHPC has a dense skeleton structure, a large amount of cementitious materials are required. At the same time, under the premise of low water-cement ratio, higher requirements are placed on water reducers, resulting in UHPC being unable to be widely used in domestic structural engineering due to its high material cost. Compared with ordinary concrete, the high cost of UHPC is due to the large amount of cement used. The cement content is usually 800~1000kg / m 3 ,How to reduce the cost is an important issue that UHPC needs to solve.
[0003] Fine aggregate is an important component of UHPC. Its particle shape significantly affects the filling density of the matrix and the demand for water. At present, quartz sand has the best effect. Because quartz sand has a large bearing capacity, it helps to maintain the stability of the matrix; and because it is an inert material, it can resist weathering and improve the durability of UHPC. However, the large-scale use of extremely fine and high-quality quartz sand is another factor that causes the high cost of UHPC. Because the extraction, grinding and refining process of this fine and high-quality fine aggregate is an energy-intensive and high-input process, and the production of quartz sand will have adverse effects on the environment such as carbon dioxide emissions, vegetation destruction, soil degradation, and dust pollution. In today's advocacy of "adapting measures to local conditions" and "green environmental protection", the focus of civil engineering materials should be shifted towards the direction of convenient material acquisition and low-carbon environmental protection.
[0004] The shrinkage of UHPC is also a major factor that restricts its application in prefabricated components. Due to the low water-cement ratio of UHPC, the large amount of active cementitious materials used, and the fact that most of them do not contain coarse aggregates, its shrinkage characteristics are very different from those of ordinary concrete. The shrinkage of UHPC is often greater than that of ordinary concrete, and it is generally accompanied by large autogenous shrinkage during the process of coagulation and hardening and service after hardening, and the risk of early cracking is very high. The shrinkage of concrete will cause uneven deformation of the overall structure of the building, resulting in cracks, which will have a great impact on the life of the structure. Therefore, the shrinkage problem is one of the important factors restricting its engineering application. Summary of the invention
[0005] In view of this, the present invention aims to provide a low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete and a preparation method thereof. The ultra-high performance concrete provided by the present invention has high strength, good toughness, low shrinkage, and has the advantages of low cost and green environmental protection.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a low-shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete, which is prepared from the following raw materials in parts by mass:
[0008] 300~320 parts of Portland cement;
[0009] Fly ash 510~520 parts;
[0010] Mineral powder 100~120 parts;
[0011] Silica fume 100~120 parts;
[0012] 350-370 parts of aeolian sand;
[0013] 760~800 parts of recycled fine aggregate;
[0014] 390-410 parts of recycled coarse aggregate;
[0015] 150~160 parts of 12mm end hook steel fiber;
[0016] 35~45 parts of 35mm end hook steel fiber;
[0017] 2~3 parts of polyether defoamer;
[0018] 25-35 parts of magnesium oxide expansion agent;
[0019] 4~5 parts of shrinkage reducing agent;
[0020] Polycarboxylate water reducer 10-12 parts;
[0021] 160~170 parts of water;
[0022] The aeolian sand includes 0.125-0.212 mm aeolian sand and 0.212-0.425 mm aeolian sand;
[0023] The recycled fine aggregate includes 0.425-0.85 mm recycled fine aggregate, 0.85-2.0 mm recycled fine aggregate and 2.0-4.75 mm recycled fine aggregate;
[0024] The particle size of the recycled coarse aggregate is 4.75-9.5 mm.
[0025] Preferably, the method for preparing the recycled fine aggregate and recycled coarse aggregate comprises the following steps:
[0026] After the abandoned bridge box beam is demolished, the obtained concrete blocks are crushed, screened, cleaned, and impurities are removed to obtain recycled fine aggregate and recycled coarse aggregate respectively;
[0027] The 28d compressive strength of concrete used to prepare box girders for bridges shall be ≥60MPa.
[0028] Preferably, the mass ratio of the 0.125-0.212 mm aeolian sand, 0.212-0.425 mm aeolian sand, 0.425-0.85 mm recycled fine aggregate, 0.85-2.0 mm recycled fine aggregate and 2.0-4.75 mm recycled fine aggregate is 1.5-2.5:2-3:2-3:1.5-2.5:1-2.
[0029] Preferably, the average particle size of the silica fume is 0.1-0.15 μm, and the specific surface area is ≥19000 m 2 / kg;
[0030] The specific surface area of the fly ash is ≥470m 2 / kg;
[0031] The mineral powder is S95 grade mineral powder with a specific surface area of ≥440m 2 / kg.
[0032] Preferably, the diameter of the 12 mm end hook type steel fiber is 0.2 mm; the diameter of the 35 mm end hook type steel fiber is 1 mm.
[0033] Preferably, the shrinkage reducing agent is a powdered shrinkage reducing agent based on alkyl glycol.
[0034] The present invention provides a method for preparing the above-mentioned low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete, comprising the following steps:
[0035] (1) Aeolian sand with a particle size of 0.125-0.212 mm, aeolian sand with a particle size of 0.212-0.425 mm, recycled fine aggregate with a particle size of 0.425-0.85 mm, recycled fine aggregate with a particle size of 0.85-2.0 mm, and recycled fine aggregate with a particle size of 2.0-4.75 mm are mixed to obtain mixed fine aggregate;
[0036] (2) dry-mixing silicate cement, fly ash, mineral powder, silica fume, polyether defoamer, magnesium oxide expansion agent and shrinkage reducing agent to obtain a mixed dry material;
[0037] (3) mixing a polycarboxylate water-reducing agent, water, and the mixed dry material to obtain a first mixed blank;
[0038] (4) mixing the mixed fine aggregate, recycled coarse aggregate and the first mixed stock to obtain a second mixed stock;
[0039] (5) mixing the 12 mm end hook steel fiber and the 35 mm end hook steel fiber with the second mixed blank to obtain a concrete slurry;
[0040] (6) curing the concrete slurry to obtain low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete;
[0041] There is no time sequence restriction between steps (1) and (2).
[0042] Preferably, the mixing method of step (4) comprises:
[0043] The mixed fine aggregate is added to the first mixed blank in multiple times, and after the obtained mixture is transformed from a pure paste state to a mortar state, the recycled coarse aggregate is added and stirred.
[0044] Preferably, the mixing time in step (3) is 3 to 5 minutes.
[0045] Preferably, the mixing time in step (5) is 3 to 5 minutes.
[0046] The invention provides a low-shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete, which is prepared from the following raw materials in parts by weight: 300-320 parts of silicate cement; 510-520 parts of fly ash; 100-120 parts of mineral powder; 100-120 parts of silica ash; 350-370 parts of aeolian sand; 760-800 parts of recycled fine aggregate; 390-410 parts of recycled coarse aggregate; 150-160 parts of 12mm end hook steel fiber; 35-45 parts of 35mm end hook steel fiber; polyether defoaming agent; 2~3 parts of agent; 25~35 parts of magnesium oxide expansion agent; 4~5 parts of shrinkage reducing agent; 10~12 parts of polycarboxylic acid water reducer; 160~170 parts of water; the aeolian sand includes 0.125~0.212mm aeolian sand and 0.212~0.425mm aeolian sand; the recycled fine aggregate includes 0.425~0.85mm recycled fine aggregate, 0.85~2.0mm recycled fine aggregate and 2.0~4.75mm recycled fine aggregate; the particle size of the recycled coarse aggregate is 4.75~9.5mm. Compared with the existing ultra-high performance concrete, the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention has the following beneficial effects:
[0047] The present invention uses a large amount of fly ash to replace part of the cement as a cementitious material, which can not only reduce the amount of cement by about 50%, thereby effectively reducing costs, but also give full play to its volcanic ash activity and particle filling effect, and can also reduce carbon dioxide emissions. The product of the volcanic ash reaction can not only play a cementing role to provide strength, but also play a role in filling pores, which is beneficial to the improvement of later mechanical properties and durability. In addition, fly ash from thermal power plants is a solid waste material. The present invention can achieve the concept of sustainable development by consuming large amounts of industrial solid waste, thereby protecting the environment and contributing to the "dual carbon" goals.
[0048] The present invention uses aeolian sand and recycled fine aggregate to optimize the gradation to replace traditional quartz sand, which can reasonably develop and utilize desert resources and waste building materials. The crushed recycled fine aggregate contains more hydration products than traditional aggregates, and the calcium hydroxide in the hydration product will undergo a secondary volcanic ash reaction after contact with mineral admixtures (silicon ash, fly ash, and mineral powder), and continue to generate calcium silicate hydrate gel (CSH), which can improve the interface transition zone between aggregates and cementitious materials, and the mixed fine aggregate after gradation optimization makes the internal structure of UHPC more compact. In addition, the use of mixed fine aggregate can not only provide an optional way for the on-site optimization of local materials and waste building materials, but also reduce carbon emissions and transportation costs compared to the use of traditional quartz sand.
[0049] The invention adds recycled coarse aggregate to the UHPC matrix, which not only provides a good mechanical skeleton for UHPC, but also reduces the amount of cementitious materials, thereby reducing the amount of cement paste per unit volume, thereby reducing the shrinkage caused by cement hydration; on the other hand, the high water absorption rate of recycled coarse aggregate can play a certain role as a water reservoir and volume fixation, and has a certain inhibitory effect on the shrinkage of the surrounding cement paste. Therefore, the introduction of recycled aggregate reduces the consumption of cementitious materials and natural aggregates, and has a promoting effect on energy conservation and emission reduction.
[0050] Since the addition of coarse aggregates into UHPC will reduce the flexural strength to a certain extent, the addition of long steel fibers to the UHPC system in the present invention can exert the synergistic toughening effect with fine steel fibers, and at the same time can increase the anchoring effect between the fibers and the aggregates, thereby improving the flexural strength.
[0051] The present invention adds concrete admixtures such as expansion agent and shrinkage reducer into the ultra-high performance concrete raw material system, gives full play to the shrinkage reduction synergistic effect between the admixture and the recycled coarse aggregate, and finally obtains an ultra-high performance concrete with low shrinkage and good engineering applicability.
[0052] The results of the embodiments show that the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention has a 7d compressive strength of 86.95MPa, a 28d compressive strength of 110.06MPa, and a 90d compressive strength of 121.34MPa; a 28d flexural strength of 16.76MPa, and a 90d flexural strength of 19.80MPa; a 3d autogenous shrinkage final value of 96.33με, and a 28d drying shrinkage final value of 60.38με. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 The flow chart for the preparation of low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete;
[0054] Figure 2 It is the gradation curve of recycled coarse aggregate and recycled fine aggregate;
[0055] Figure 3 is the thermogravimetric curve of recycled aggregate;
[0056] Figure 4 This is a comparison chart of the compressive strength of different specimens;
[0057] Figure 5 Comparison chart of flexural strength of different specimens;
[0058] Figure 6 This is a comparison chart of the autogenous shrinkage of different specimens;
[0059] Figure 7 This is a comparison chart of drying shrinkage of different specimens. DETAILED DESCRIPTION
[0060] The present invention provides a low-shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete, which is prepared from the following raw materials in parts by mass:
[0061] 300~320 parts of Portland cement;
[0062] Fly ash 510~520 parts;
[0063] Mineral powder 100~120 parts;
[0064] Silica fume 100~120 parts;
[0065] 350-370 parts of aeolian sand;
[0066] 760~800 parts of recycled fine aggregate;
[0067] 390-410 parts of recycled coarse aggregate;
[0068] 150~160 parts of 12mm end hook steel fiber;
[0069] 35~45 parts of 35mm end hook steel fiber;
[0070] 2~3 parts of polyether defoamer;
[0071] 25-35 parts of magnesium oxide expansion agent;
[0072] 4~5 parts of shrinkage reducing agent;
[0073] Polycarboxylate water reducer 10-12 parts;
[0074] 160~170 parts of water;
[0075] The aeolian sand includes 0.125-0.212 mm aeolian sand and 0.212-0.425 mm aeolian sand;
[0076] The recycled fine aggregate includes 0.425-0.85 mm recycled fine aggregate, 0.85-2.0 mm recycled fine aggregate and 2.0-4.75 mm recycled fine aggregate;
[0077] The particle size of the recycled coarse aggregate is 4.75-9.5 mm.
[0078] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0079] In terms of mass fraction, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 300-320 parts of Portland cement, preferably 305-315 parts, and more preferably 306 parts. In the present invention, the Portland cement is preferably P·II 52.5 type cement, and the measured 28d compressive strength of the cement is preferably ≥59.1MPa.
[0080] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 510-520 parts of fly ash, and more preferably 510-515 parts. In the present invention, the fly ash is a fine silica-alumina microbead granular material, which can effectively improve many properties of concrete due to its morphological effect, filling effect and volcanic ash effect. In the present invention, the fly ash is preferably Class I fly ash provided by a thermal power plant, with a gray appearance and a specific surface area of preferably ≥470m 2 / kg, more preferably 472m 2 / kg. Fly ash is a byproduct of coal combustion in thermal power plants. It is also the most commonly used mineral admixture in concrete. The particle size of fly ash is similar to that of cement. Replacing part of cement with a large amount of fly ash as a cementitious material can play a role in particle filling and volcanic ash activity. The product of the volcanic ash reaction of fly ash can not only play a role in cementation to provide strength, but also play a role in filling pores, which is conducive to improving mechanical properties and durability.
[0081] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 100 to 120 parts of mineral powder, and more preferably 108 parts. In the present invention, the mineral powder is preferably industrial waste slag produced by blast furnace ironmaking. In the present invention, the mineral powder is preferably S95 grade mineral powder, and the specific surface area is preferably ≥440m 2 / kg, more preferably 446m 2 In the present invention, the mineral powder is added to UHPC as a mineral admixture to reduce the amount of cement used, and effectively reduce the production cost of UHPC and the degree of environmental pollution.
[0082] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 100 to 120 parts of silica fume, and more preferably 108 parts. In the present invention, the silica fume is preferably in the form of gray-black powder, with an average particle size of preferably 0.1 to 0.15 μm and a specific surface area of preferably ≥19000 m 2 / kg, more preferably 19530m 2 / kg.
[0083] Based on the mass fraction of the silicate cement, the raw material for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention includes 350-370 parts of aeolian sand, preferably 355-360 parts, and more preferably 357 parts. In the present invention, the aeolian sand preferably includes 0.125-0.212 mm aeolian sand and 0.212-0.425 mm aeolian sand, and the mass ratio of the two is preferably 1.5-2.5:2-3, and more preferably 1.5:2.
[0084] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 760 to 800 parts of recycled fine aggregate, and more preferably 765 to 780 parts. In the present invention, the recycled fine aggregate includes 0.425 to 0.85 mm recycled fine aggregate, 0.85 to 2.0 mm recycled fine aggregate, and 2.0 to 4.75 mm recycled fine aggregate, and the mass ratio is preferably 2 to 3: 1.5 to 2.5: 1 to 2, and more preferably 3: 2.5: 1. In the present invention, the raw material for preparing the recycled fine aggregate is concrete of abandoned box girders for bridges. In the present invention, the abandoned box girder concrete is crushed and added to UHPC as aggregate to achieve high-value utilization of recycled aggregates in high-strength concrete, which is green, low-carbon and environmentally friendly.
[0085] Aeolian sand is a kind of ultra-fine sand mainly found in deserts and Gobi. It has a very low moisture content and uniform fine particles. Its main components are SiO2 and Al2O3. If desert resources can be reasonably developed and utilized, it can not only curb land desertification and protect the natural environment, but also reduce the collection and transportation costs of engineering sand and reasonably reduce the cost of engineering. However, aeolian sand has poor grading, concentrated particle size, and high mud content. The fineness modulus of desert sand is generally less than 1.5, or the average particle size is less than 0.25mm, which is ultra-fine sand, much finer than the sand commonly used in construction projects, and does not meet the requirements of construction sand standards. Therefore, it is necessary to optimize the grading of aeolian sand, and recycled fine aggregate can perfectly undertake this task. On the one hand, the utilization of recycled aggregate is generally concentrated in the direction of coarse aggregate with a particle size greater than 5mm, and recycled fine aggregate is discarded as a by-product, resulting in a huge waste of resources. On the other hand, compared with traditional natural aggregate, recycled fine aggregate contains a large amount of cement hydration products, among which the hydroxide ion (OH -) can provide a basis for the activation of mineral admixtures, thereby improving early strength. In the present invention, the recycled fine aggregate and aeolian sand constitute fine aggregate. In the present invention, the mass ratio of 0.125~0.212mm aeolian sand, 0.212~0.425mm aeolian sand, 0.425~0.85mm recycled fine aggregate, 0.85~2.0mm recycled fine aggregate and 2.0~4.75mm recycled fine aggregate is .5~2.5:2~3:2~3:1.5~2.5:1~2, more preferably 1.5:2:3:2.5:1, and the best gradation is formed under this ratio.
[0086] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 390 to 410 parts of recycled coarse aggregate, preferably 395 to 400 parts. In the present invention, the raw material for preparing the recycled coarse aggregate is the concrete of abandoned box girders for bridges. A direct and effective way to reduce the shrinkage of UHPC is to add coarse aggregate to the system. The addition of coarse aggregate can reduce the amount of cementitious material so that the cement slurry content per unit volume is reduced, thereby reducing the self-shrinkage caused by cement hydration; on the other hand, coarse aggregate can be regarded as a component with a fixed volume in cement-based materials, which has a certain inhibitory effect on the self-shrinkage of the surrounding cement slurry. In addition, the higher water absorption rate of recycled coarse aggregate can also act as a reservoir to reduce the self-shrinkage of UHPC.
[0087] In the present invention, the particle size of the recycled coarse aggregate is 4.75-9.5 mm. The recycled coarse aggregate and fine aggregate under this particle size can form a continuous gradation, thereby achieving the purpose of making UHPC dense.
[0088] In the present invention, the method for preparing the recycled fine aggregate and recycled coarse aggregate preferably comprises the following steps:
[0089] The box girders of abandoned bridges are dismantled, and the obtained concrete blocks are crushed, screened, cleaned, and impurities are removed to obtain recycled fine aggregate and recycled coarse aggregate, namely 0.425-0.85mm recycled fine aggregate, 0.85-2.0mm recycled fine aggregate, 2.0-4.75mm recycled fine aggregate, and 4.75-9.5mm recycled coarse aggregate.
[0090] The present invention preferably uses abandoned box girders for bridges as raw materials for preparing recycled fine aggregate and recycled coarse aggregate. In the present invention, the 28d compressive strength of the concrete used to prepare the box girders for bridges is preferably ≥60MPa. The present invention has no special requirements for the specific operation mode of the crushing and screening, and the crushing and screening methods well known in the art can be used. In the process of crushing and screening, impurities in the concrete are removed, and then the needle-like and flaky particles therein are removed to meet the crushing value of less than 15%.
[0091] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 150 to 160 parts of 12 mm end hook steel fibers, preferably 156 parts. In the present invention, the 12 mm end hook steel fibers are preferably end hook copper-plated steel fibers. In the present invention, the diameter of the 12 mm end hook steel fibers is preferably 0.2 mm, and the tensile strength is preferably ≥ 2800 MPa.
[0092] Based on the mass fraction of the silicate cement, the raw material for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention includes 35 to 45 parts of 35 mm end hook steel fiber, preferably 39 parts. In the present invention, the 35 mm end hook steel fiber is preferably an end hook copper-plated steel fiber. In the present invention, the diameter of the 35 mm end hook steel fiber is preferably 1 mm.
[0093] In the present invention, the long fiber not only has an anchoring effect on the coarse aggregate of UHPC, but also has an inhibitory effect on the shrinkage of UHPC within a 2% dosage. At the same time, the engineering cost of the long fiber is reduced compared to that of the short fiber, and the cost can be further reduced at the same steel fiber dosage. The present invention uses 35mm end hook steel fiber as the doping fiber, the purpose of which is to improve the flexural fracture toughness of concrete.
[0094] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 2 to 3 parts of a polyether defoamer, preferably 2.6 parts. In the present invention, the effective content of the defoamer is preferably ≥ 60%.
[0095] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 25 to 35 parts of magnesium oxide expansion agent, more preferably 30 parts. In the present invention, the content of magnesium oxide in the magnesium oxide expansion agent is preferably ≥30%.
[0096] As a specific embodiment of the present invention, the index parameters of the magnesium oxide expansion agent are shown in Table 1.
[0097] Table 1 Index parameters of magnesium oxide expansion agents
[0098]
[0099] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 4 to 5 parts of shrinkage reducer, preferably 4.5 parts. In the present invention, the shrinkage reducer is preferably a powdered shrinkage reducer based on alkyl glycol. As a specific embodiment of the present invention, the shrinkage reducer is BASF R+D CureStar SRA 8710 F shrinkage reducer, purchased from Nanjing Qinghai Trading Co., Ltd.
[0100] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 10 to 12 parts of polycarboxylate water reducer, preferably 10.2 parts. In the present invention, the solid content of the polycarboxylate water reducer is preferably 40%, and the water reduction rate is preferably 39%.
[0101] Based on the mass fraction of the silicate cement, the raw materials for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete provided by the present invention include 160 to 170 parts of water, preferably 163.2 parts. In the present invention, the water is preferably tap water.
[0102] The present invention provides a method for preparing the above-mentioned low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete, comprising the following steps:
[0103] (1) Aeolian sand with a particle size of 0.125-0.212 mm, aeolian sand with a particle size of 0.212-0.425 mm, recycled fine aggregate with a particle size of 0.425-0.85 mm, recycled fine aggregate with a particle size of 0.85-2.0 mm, and recycled fine aggregate with a particle size of 2.0-4.75 mm are mixed to obtain mixed fine aggregate;
[0104] (2) dry-mixing silicate cement, fly ash, mineral powder, silica fume, polyether defoamer, magnesium oxide expansion agent and shrinkage reducing agent to obtain a mixed dry material;
[0105] (3) mixing a polycarboxylate water-reducing agent, water, and the mixed dry material to obtain a first mixed blank;
[0106] (4) mixing the mixed fine aggregate, recycled coarse aggregate and the first mixed stock to obtain a second mixed stock;
[0107] (5) mixing the 12 mm end hook steel fiber and the 35 mm end hook steel fiber with the second mixed blank to obtain a concrete slurry;
[0108] (6) curing the concrete slurry to obtain low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete;
[0109] There is no time sequence restriction between steps (1) and (2).
[0110] The present invention mixes aeolian sand with a particle size of 0.125-0.212 mm, aeolian sand with a particle size of 0.212-0.425 mm, recycled fine aggregate with a particle size of 0.425-0.85 mm, recycled fine aggregate with a particle size of 0.85-2.0 mm, and recycled fine aggregate with a particle size of 2.0-4.75 mm to obtain mixed fine aggregate. In the present invention, the mixing is preferably performed in a mixer.
[0111] In the present invention, silicate cement, fly ash, mineral powder, silica fume, polyether defoamer, magnesium oxide expansion agent and shrinkage reducing agent are dry mixed to obtain a mixed dry material. In the present invention, the dry mixing is preferably carried out in a forced concrete mixer. In the present invention, the dry mixing time is preferably 1 to 2 minutes, more preferably 2 minutes.
[0112] The present invention mixes the polycarboxylate water-reducing agent, water and the mixed dry materials to obtain a first mixed stock. In the present invention, the mixing is preferably stirring and mixing, and the mixing time is preferably 3 to 5 minutes, more preferably 4 minutes.
[0113] The present invention mixes the mixed fine aggregate, recycled coarse aggregate and the first mixed stock to obtain a second mixed stock. In the present invention, the mixing method preferably includes:
[0114] The mixed fine aggregate is added to the first mixed blank in multiple times, and after the obtained mixture is transformed from a pure paste state to a mortar state, the recycled coarse aggregate is added and stirred.
[0115] In the present invention, after the mixed fine aggregate is added to the first mixed stock in multiple times, the present invention preferably continues stirring for 1 minute. In the present invention, the time for adding the recycled coarse aggregate for stirring is preferably 3 to 5 minutes, more preferably 4 minutes.
[0116] In the present invention, 12 mm end hook steel fiber and 35 mm end hook steel fiber are mixed with the second mixed blank to obtain a concrete slurry. In the present invention, the mixing is preferably stirring and mixing, and the mixing time is preferably 3 to 5 minutes, more preferably 4 minutes.
[0117] The present invention performs curing on the concrete slurry to obtain low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete. In the present invention, the curing condition is preferably standard curing.
[0118] As a specific embodiment of the present invention, the preparation flow chart of the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete is as follows: Figure 1 shown.
[0119] The low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete and its preparation method provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0120] Example 1
[0121] (1) Raw material preparation
[0122] The following raw materials are used in the embodiments of the present invention:
[0123] ①Cement, silica fume, fly ash and mineral powder. Their chemical compositions are shown in Table 2.
[0124] The silicate cement used was P·II 52.5 type cement, and the measured 28d compressive strength was 59.1MPa. The performance indicators are shown in Table 3.
[0125] The silica fume is produced by a company in Shanghai. It is a gray-black powder with an average particle size of 0.1~0.15μm and a specific surface area of 19530m 2 / kg.
[0126] The fly ash is grade I fly ash provided by the thermal power plant. It is gray in appearance and has a specific surface area of 472m 2 / kg.
[0127] The mineral powder is S95 grade mineral powder with a specific surface area of 446m 2 / kg.
[0128] Table 2 Chemical composition of cement, silica fume and mineral powder
[0129]
[0130] Table 3 Cement performance indicators
[0131]
[0132] ② Recycled coarse aggregate and recycled fine aggregate are made from abandoned bridge box girder concrete with a 28d compressive strength greater than 60MPa. The concrete is crushed and sieved, and then the impurities and needle-like and flaky particles are removed after cleaning to obtain 0.425~0.85mm recycled fine aggregate, 0.85~2.0mm recycled fine aggregate, 2.0~4.75mm recycled fine aggregate, and 4.75~9.5mm recycled coarse aggregate. The grading curve of recycled coarse aggregate and recycled fine aggregate is shown in the figure below: Figure 2 shown.
[0133] The fine aggregate is made of aeolian sand with particle sizes ranging from 0.125 to 0.212 mm, aeolian sand with particle sizes ranging from 0.212 to 0.425 mm, recycled fine aggregate with particle sizes ranging from 0.425 to 0.85 mm, recycled fine aggregate with particle sizes ranging from 0.85 to 2.0 mm, and recycled fine aggregate with particle sizes ranging from 2.0 to 4.75 mm in a graded manner of 1.5:2:3:2.5:1.
[0134] In order to find out whether recycled aggregates can improve the early strength of UHPC, thermogravimetric tests were carried out on recycled aggregates. Figure 3 The thermogravimetric curve of recycled aggregate. It can be seen that the main effect of recycled aggregate in improving strength at the microscopic level is that the Ca(OH)2 in it will react with mineral admixtures to produce new calcium silicate hydrate gel (CSH), so it is necessary to find out the Ca(OH)2 content in the aggregate. Ca(OH)2 has a thermal decomposition reaction at about 430℃ as shown in Formula 1:
[0135] Ca(OH)2→CaO +H2O Formula 1;
[0136] According to the reaction equation, the Ca(OH)2 content can be calculated according to formula 2:
[0137] Formula 2;
[0138] In formula 2, M loss The mass loss caused by the thermal reaction at about 430℃; M remain is the residual mass of the experimental sample after thermal decomposition at 1000℃.
[0139] According to the above formula, the Ca(OH)2 content of recycled aggregate is 5.45%. The results show that the addition of recycled aggregate to UHPC will provide a basis for the activation of mineral admixtures and promote the development of its strength.
[0140] ③12mm end hook type steel fiber is an end hook shaped copper-plated steel fiber with a diameter of 0.2mm and a tensile strength of 2800MPa; the diameter of the 35mm end hook type steel fiber is 1mm.
[0141] ④ The water reducing agent uses a polycarboxylic acid high-efficiency water reducing agent produced by a company in Wuhan, with a solid content of 40% and a water reduction rate of 39%. The expansion agent uses a magnesium expansion agent with a magnesium oxide content greater than or equal to 30%. The shrinkage reducing agent uses a powdered shrinkage reducing agent based on alkyl glycol, and the defoaming agent uses a polyether defoaming agent with an effective content greater than 60%.
[0142] (2) Low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete includes the following raw materials in parts by weight:
[0143] 306 parts of Portland cement; 510 parts of fly ash; 108 parts of mineral powder; 108 parts of silica fume; 357 parts of aeolian sand; 765 parts of recycled fine aggregate; 395 parts of recycled coarse aggregate; 156 parts of 12mm end hook type steel fiber; 39 parts of 35mm end hook type steel fiber; 2.6 parts of polyether defoamer; 30 parts of magnesium oxide expansion agent; 4.5 parts of shrinkage reducing agent; 10.2 parts of polycarboxylic acid high-efficiency water reducing agent; 163.2 parts of tap water.
[0144] The preparation method adopts the following steps:
[0145] S1. Pour 153 parts of aeolian sand with a particle size of 0.125mm-0.212mm, 204 parts of aeolian sand with a particle size of 0.212mm-0.425mm, 306 parts of recycled fine aggregate with a particle size of 0.425mm-0.85mm, 255 parts of recycled fine aggregate with a particle size of 0.85mm-2.0mm, and 102 parts of recycled fine aggregate with a particle size of 2.0mm-4.75mm into a mixer and mix them thoroughly to obtain mixed fine aggregate.
[0146] S2. According to the weight ratio, 306 parts of ordinary Portland cement, 510 parts of fly ash, 108 parts of mineral powder, 108 parts of silica fume, 2.6 parts of polyether defoamer, 30 parts of magnesium oxide expansion agent, and 4.5 parts of shrinkage reducer are placed in a forced concrete mixer and dry mixed for 1 minute to obtain mixed dry material 1.
[0147] S3. Add 10.2 parts of high-efficiency water reducer to 163.2 parts of tap water, stir evenly and pour into the mixed dry material 1 obtained in step S2, continue stirring for 3-5 minutes, and obtain mixed stock 2.
[0148] S4. Slowly add the mixed fine aggregate obtained in step S1 to the mixed blank 2 for multiple times, and continue stirring for 1 minute. After the mixture is transformed from a pure paste state to a mortar state, add the recycled coarse aggregate to the mixture and continue stirring for 3 to 5 minutes. It is necessary to ensure that the aggregate is evenly dispersed in the concrete system to obtain a mixed blank 3.
[0149] S5. Add 156 parts of 12 mm steel fiber and 39 parts of 35 mm steel fiber to the mixed blank obtained in step S4, and continue stirring for 3 to 5 minutes to obtain concrete slurry.
[0150] S6. Pour the concrete slurry obtained in step S5 into a test mold, and after curing to the age, obtain a low-shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete body, which is recorded as specimen GX1.
[0151] Example 2
[0152] According to the raw material ratio in Table 4, the preparation process was the same as that in Example 1 to obtain a low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete body, which was recorded as specimen GX2.
[0153] Example 3
[0154] According to the raw material ratio in Table 4, the preparation process was the same as that in Example 1 to obtain a low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete body, which was recorded as specimen GX3.
[0155] Comparative Example
[0156] According to the raw material ratio in Table 4, the control example JZ (conventional UHPC part), the control example FM (replacing a large amount of cement with fly ash), the control example FM (replacing quartz sand with aeolian sand and recycled aggregate), the control example XW (adding basalt aggregate), the control example ZS (adding recycled coarse aggregate), the example 1 GX1 (mixed with 35mm end hook steel fiber, adding expansion agent, shrinkage reducer, defoaming agent), the example 2 GX2 (adjusting the mixing ratio), and the example 3 GX3 (adjusting the mixing ratio) were prepared. In Table 4, the unit of the amount of raw materials added is kg / m 3 .
[0157] Table 4 Raw material ratios of the examples and comparative examples
[0158]
[0159] The concrete obtained in the embodiment and the comparative example was cured for different days. After the curing, the compressive strength and flexural strength were tested according to the "Test Method for Mechanical Properties of Ordinary Concrete" (GB / T 50081), and the 72h autogenous shrinkage and drying shrinkage were tested according to the contact method in the "Test Code for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020). The results are shown in Table 5 and Figures 4 to 7 As shown, Figure 4 The compressive strength comparison chart of different specimens is shown in Figure 2. Figure 5 Comparison of flexural strength of different specimens. Figure 6 The comparison chart of autogenous shrinkage of different specimens is shown in Figure 2. Figure 7 This is a comparison chart of drying shrinkage of different specimens.
[0160] Table 5 Performance test results of concrete obtained from examples and comparative examples
[0161]
[0162] The experimental results show that replacing cement with a large amount of fly ash will lead to a decrease in compressive strength. Compared with the JZ experimental group, the fly ash content is 600kg / m 3The 7d, 28d, and 90d cube compressive strengths of the FM experimental group decreased by 16%, 13.62%, and 8.44%, respectively. However, its 90d compressive strength still reached 124.7MPa, and the cement dosage was reduced by 240kg / m 3 This is because only part of the cement in the UHPC system participates in the hydration reaction, and the rest of the cement only serves as a filler. Therefore, it is feasible to replace the unhydrated part of the cement with an appropriate amount of fly ash as a filler. This method can reduce the production cost of UHPC.
[0163] The results of the FJ experimental group showed that replacing the traditional quartz sand fine aggregate with optimized graded aeolian sand and recycled fine aggregate can improve the strength of UHPC. This is because the introduction of crushed recycled fine aggregate can provide fly ash with hydroxide ions (OH - ), and fly ash can combine with it to generate new colloidal substances such as CSH. In addition, the coarse aggregate forms a rigid skeleton with good integrity inside the UHPC matrix, and the bite force between the aggregates is enhanced. In addition, the anchoring effect of the steel fiber between the coarse aggregate and the matrix makes the overall performance of the system better. At the same time, the addition of coarse aggregate can effectively reduce the shrinkage of UHPC. This is because the addition of coarse aggregate will reduce the amount of cementitious materials in UHPC, and at the same time, it will form a skeleton structure in UHPC, which can be regarded as a fixed volume component in UHPC, which improves its volume stability and inhibits the self-shrinkage of the surrounding cement paste. Compared with the basalt coarse aggregate experimental group XW, the shrinkage reduction effect of the recycled coarse aggregate experimental group ZS is more obvious. The reduction in the autogenous shrinkage of the recycled aggregate is 47.33% greater than that of the basalt. The reason for this phenomenon is that the water absorption rate of the recycled coarse aggregate is much greater than that of the basalt coarse aggregate. The water absorption rate of the recycled aggregate is 7.04%, while the water absorption rate of the basalt is only 0.635%. The large water absorption rate of the recycled aggregate ensures the stability of the relative humidity inside the UHPC and plays a certain role in internal maintenance.
[0164] In addition, although the early strength of the experimental group ZS with recycled aggregate and aeolian sand was slightly reduced compared with the experimental group JZ with quartz sand, its volume stability was significantly improved, and the production cost and carbon dioxide emissions of UHPC were also reduced, which proved the practicality, environmental protection and economy of introducing recycled aggregate into the UHPC system.
[0165] According to the results of the GX1, GX2, and GX3 experimental groups, the impact of changing the raw material dosage within the appropriate range is not significant. Taking into account the mechanical properties and volume stability performance, the experimental group GX1 is the most preferred. On the basis of adding recycled coarse aggregate, its flexural strength can be improved by mixing 32mm steel fiber. At the same time, through admixtures such as expansion agents, shrinkage reducers, and defoaming agents, the ultra-high performance concrete has a lower shrinkage rate and better engineering applicability.
[0166] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete, characterized in that: Prepared from the following raw materials in parts by weight: 300~320 parts of Portland cement; Fly ash 510~520 parts; Mineral powder 100~120 parts; Silica fume 100~120 parts; 350-370 parts of aeolian sand; 760~800 parts of recycled fine aggregate; 390-410 parts of recycled coarse aggregate; 150~160 parts of 12mm end hook steel fiber; 35~45 parts of 35mm end hook steel fiber; 2~3 parts of polyether defoamer; 25-35 parts of magnesium oxide expansion agent; 4~5 parts of shrinkage reducing agent; Polycarboxylate water reducer 10-12 parts; 160~170 parts of water; The aeolian sand includes 0.125-0.212 mm aeolian sand and 0.212-0.425 mm aeolian sand; The recycled fine aggregate includes 0.425-0.85 mm recycled fine aggregate, 0.85-2.0 mm recycled fine aggregate and 2.0-4.75 mm recycled fine aggregate; The particle size of the recycled coarse aggregate is 4.75-9.5 mm; The mass ratio of the 0.125-0.212 mm aeolian sand, 0.212-0.425 mm aeolian sand, 0.425-0.85 mm recycled fine aggregate, 0.85-2.0 mm recycled fine aggregate and 2.0-4.75 mm recycled fine aggregate is 1.5-2.5:2-3:2-3:1.5-2.5:1-2.
2. The low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: The method for preparing the recycled fine aggregate and recycled coarse aggregate comprises the following steps: After the abandoned bridge box beam is demolished, the obtained concrete blocks are crushed, screened, cleaned, and impurities are removed to obtain recycled fine aggregate and recycled coarse aggregate respectively; The 28d compressive strength of concrete used to prepare box girders for bridges shall be ≥60MPa.
3. The low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: The average particle size of the silica fume is 0.1-0.15 μm, and the specific surface area is ≥19000 m 2 / kg; The specific surface area of the fly ash is ≥470m 2 / kg; The mineral powder is S95 grade mineral powder with a specific surface area of ≥440m 2 / kg.
4. The low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: The diameter of the 12mm end hook type steel fiber is 0.2mm; the diameter of the 35mm end hook type steel fiber is 1mm.
5. The low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: The shrinkage reducing agent is a powdered shrinkage reducing agent based on alkyl glycol.
6. The method for preparing the low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete according to any one of claims 1 to 5, comprising the following steps: (1) Aeolian sand with a particle size of 0.125-0.212 mm, aeolian sand with a particle size of 0.212-0.425 mm, recycled fine aggregate with a particle size of 0.425-0.85 mm, recycled fine aggregate with a particle size of 0.85-2.0 mm, and recycled fine aggregate with a particle size of 2.0-4.75 mm are mixed to obtain mixed fine aggregate; (2) dry-mixing silicate cement, fly ash, mineral powder, silica fume, polyether defoamer, magnesium oxide expansion agent and shrinkage reducing agent to obtain a mixed dry material; (3) mixing a polycarboxylate water-reducing agent, water, and the mixed dry material to obtain a first mixed blank; (4) mixing the mixed fine aggregate, recycled coarse aggregate and the first mixed stock to obtain a second mixed stock; (5) mixing the 12 mm end hook steel fiber and the 35 mm end hook steel fiber with the second mixed blank to obtain a concrete slurry; (6) curing the concrete slurry to obtain low shrinkage hybrid steel fiber recycled aggregate ultra-high performance concrete; There is no time sequence restriction between steps (1) and (2).
7. The preparation method according to claim 6, characterized in that: The mixing method of step (4) comprises: The mixed fine aggregate is added to the first mixed blank in multiple times, and after the obtained mixture is transformed from a pure paste state to a mortar state, the recycled coarse aggregate is added and stirred.
8. The preparation method according to claim 6, characterized in that: The mixing time in step (3) is 3 to 5 minutes.
9. The preparation method according to claim 6, characterized in that: The mixing time in step (5) is 3 to 5 minutes.
Citation Information
Patent Citations
Ultra-high performance concrete material containing coarse aggregate and preparation method thereof
CN111072348A
Machine-made sand and aeolian sand co-doped ultra-high performance concrete and preparation method thereof
CN111533504A
Cited By
Ultra-high performance concrete and preparation method thereof
CN120903892A